Website-Based Development of Learning Management System using V-Development Method Model (Case Study: UNRI, Informatics Engineering Study Program) - Salsabilla Azahra Putri; Feri Candra (JINAV: Journal of Information and Visualization, 2023)
Developers often use a software development model, namely the waterfall or classical models. Waterfall uses a systematic approach, so it tends to be archaic and will cause significant problems. The problems appeared when the process at the previous stage experiences happened, so the process could not go to the next stage. In addition, the tests were carried out for the solution to the problem. There was a need for a v-model development model. This model is the waterfall model development, then described in the form of v, and there was testing in each phase. This V-Model is an excellent model because it has good illustrations and clarity. The Website Learning Management System is built using the PHP programming language. Based on the results of the testing unit, the software used whitebox, and all units could run 100% well. Meanwhile, integration testing and testing systems using black boxes were 100% running well. Acceptance testing using ISO 25010 consisted of eight characteristics: functionality, efficiency, compatibility, usability, reliability, maintainability, security, and portability. These aspects could run well.